Activity of Enzyme in Escherichia Coli Through Molecular Techniques - Liss Dyah Dewi Arini; Fredericus Pramonodjati (Lembaga Pengembangan Kinerja Dosen, 2025)
Enzymes are protein biomolecules that act as catalysts in various biochemical reactions, both in biological systems and industrial applications. The uniqueness of enzymes lies in their ability to accelerate the rate of reactions with a high degree of specificity towards certain substrates without undergoing permanent changes in their chemical structure. Enzyme activity is strongly influenced by various environmental factors, such as temperature, pH, substrate concentration, and the presence of inhibitors or activators. Therefore, quantitative testing of enzyme activity is an important step in understanding the characteristics of enzymes and their applications in various fields. Escherichia coli produces Extended-Spectrum Β-Lactamase Enzyme (ESBL) and plays a role in damaging the structure of beta lactam antibiotics so that the antibiotics cannot kill bacteria. Bacteria that produce ESBLs need to be watched out for because ESBLs are produced by genes located on plasmids, which can easily be transferred to other bacteria, and often also carry resistance genes to other antibiotics. Objective: to accurately measure the activity or concentration of enzymes in samples of Escherichia coli bacteria and understand the influence of variables such as substrate concentration on the reaction rate. Method: spectrophotometry through enzyme extraction, making a standard curve and testing enzyme activity against variations in substrate concentration. Results: samples with concentrations of 0.1 and 0.3 showed good and appropriate absorbance results. However, in the sample 0.5 ; 0.7 ; and 1.0 indicates an absorbance number that is slightly higher than it should be. Conclusion: the enzyme in Escherichia coli bacteria has good activity at sample concentrations of 0.1 and 0.3.